Manfaat Pembangunan Melalui Kontribusi Dana Desa terhadap Kesejahteraan Masyarakat Desa - Muhammad Subandi; Didi Sudrajat; Novira Cahya Wulan Sari (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2023)
This research activity aims to obtain information about the usefulness of development results through the contribution of village funds to the welfare of rural communities. Qualitative analysis was used as a method to describe the results of the study, data were collected by using documentation and interview study techniques, and data reduction techniques, data presentation, and conclusion were used for data analysis in this research. Based on the results of the research, information was obtained that development from the contribution of village funds was carried out for activities in the field of infrastructure and facilities development, and activities in the field of village community empowerment, and the planning process the village government had involved community participation in the formulation of priorities for the use of village funds. From the results of development, it has provided benefits for the welfare of the community in the form of ease of accessibility, environmental comfort, capacity and skill improvement, as well as increased economic welfare in terms of increasing income and making it easier to meet daily needs as well as the needs of community business activities such as business activities in the agricultural sector. It can be concluded that development through the contribution of village funds is beneficial for improving the welfare of rural communities.